Social inclusion and higher education - Basit, Tehmina N; Tomlinson, Sally (Policy Press, 2012)
This book is about the experiences of students in institutions of higher education from 'non-traditional' backgrounds with contributions from the UK, the USA and Australia which reveal that the issues surrounding the inclusion of 'non-traditional' students are broadly similar in different countries.